2018
DOI: 10.26603/ijspt20180185
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Short Term Effect of Dry Needling on Triceps Surae Range of Motion and Functional Movement: A Randomized Trial

Abstract: Background: Dry needling (DN) has been established as an effective treatment for myofascial pain, however, there are no studies thus far investigating the benefit to movement and motor control. Purpose: The primary purpose of this study was to compare differences in a series of outcomes between dry needling, dry needling and stretching, and stretching only in a sample of healthy males. A secondary purpose was to compare change over time. Design: Blinded, randomized controlled trial Methods: Thirty healthy male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…No significant changes in range of motion were found, either. A single treatment session may not be enough to obtain the range of motion changes which have been reported by others [57]. In fact, differences are found when a greater number of sessions are applied [58].…”
Section: Changes In Sensory and Motor Outcomesmentioning
confidence: 87%
“…No significant changes in range of motion were found, either. A single treatment session may not be enough to obtain the range of motion changes which have been reported by others [57]. In fact, differences are found when a greater number of sessions are applied [58].…”
Section: Changes In Sensory and Motor Outcomesmentioning
confidence: 87%
“…In addition, the results reported by several authors about the ROM after a DN treatment did not match with what we found in our study. (50) (51) Therefore, further research is needed in order to a better understanding of the possible relationship between the motor control and ROM.…”
Section: Discussionmentioning
confidence: 99%
“…Consecutive weekly treatments can possibly facilitate persistent improvements and reduce the number of injuries within a season in a group of elite youth soccer players (46). Functional movements such as squatting also can be improved with needling (36); however, it was noted in this study that needling was done on one side only, and squatting obviously requires both legs, so the authors thought that needling may elicit a spinal reflex that affects both lower extremities as the mechanism of action.…”
Section: Needling For Sports Performancementioning
confidence: 90%